Evaluation of the Bioenergy Potential of Temer Musa: An Invasive Tree from the African Desert - Nikdalila Radenahmad; Md Sumon Reza; Muhammad Saifullah Abu Bakar; Shahriar Shams; Alem Tesfai; Juntakan Taweekun; Nima Khalilpoor; Abul Kalam Azad; Alibek Issakhov (International Journal of Chemical Engineering)
Temer musa (Prosopis chilensis) is an invasive wild tree found in the desert of many countries, e.g., Eritrea, Ethiopia, Sudan, India, South Africa, and the USA. The thermochemical properties of this invasive tree were analyzed as a potential biomass feedstock for energy generation. The calorific value measurement of the temer musa wood was found to be 19.83 MJ/kg. Thermogravimetric analysis and derivative weight profiles displayed that the decomposition happened in four stages representing moisture content, volatile matter, fixed carbon, and ash formation. The proximate parameters are in good range with other known biomasses and are found suitable for the thermochemical energy conversion. The gasification process confirmed the existence of several gases that are usually observed in invasive biomasses. All gasification gases were in the acceptable range, and no hydrogen sulfide gas was observed, which makes the conversion as environment friendly. The obtained results show that the energy conversion of temer musa is suitable for real-time implementation.